2017
DOI: 10.3934/publichealth.2017.5.446
|View full text |Cite
|
Sign up to set email alerts
|

The Relation among Prostate Cancer Knowledge and Psychosocial Factors for Prostate Cancer Screening among African American Men: a Correlational Study

Abstract: African American (AA) men face disproportionately higher rates of prostate cancer (PCa) in comparison to other races. In addition, higher mortality rates from PCa amongst AA men signifies PCa as a formidable health disparity. Inconsistent PCa screening guidelines among medical organizations, further clouds one's decision on receiving a PCa screening. Examining various relations among factors which influence PCa screening may provide insight into their decision whether or not to receive a PCa screening. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
(66 reference statements)
0
2
0
1
Order By: Relevance
“…En contraste con lo anterior Agbughi y col concluyo que el 22,4% de los encuestados conocían el PSA y solo el 4,5% se sometió a una prueba de PSA (17), en el estudio de Nakandi y col, un gran porcentaje de los encuestados no conocía ningún método de detección temprana de cáncer de próstata (18) también Dickey y col en su estudio identificaron un pequeño porcentaje de participantes del grupo control que a pesar de no haber recibido la intervención educativa se realizaron el tamizaje de cáncer de próstata. (19). El conocimiento en este estudio uno de los principales factores para el inicio y la continuación de los exámenes, debido a que la población estudiada mayoritariamente conocía el tema y eso llevo a una acción favorable para la realización del tamizaje.…”
Section: Discussionunclassified
“…En contraste con lo anterior Agbughi y col concluyo que el 22,4% de los encuestados conocían el PSA y solo el 4,5% se sometió a una prueba de PSA (17), en el estudio de Nakandi y col, un gran porcentaje de los encuestados no conocía ningún método de detección temprana de cáncer de próstata (18) también Dickey y col en su estudio identificaron un pequeño porcentaje de participantes del grupo control que a pesar de no haber recibido la intervención educativa se realizaron el tamizaje de cáncer de próstata. (19). El conocimiento en este estudio uno de los principales factores para el inicio y la continuación de los exámenes, debido a que la población estudiada mayoritariamente conocía el tema y eso llevo a una acción favorable para la realización del tamizaje.…”
Section: Discussionunclassified
“…e effectiveness of community-based interventions on knowledge on PC has been reported across countries [17,25,26]. A similar study reported a significant increase in prostate cancer knowledge following a community health worker-led intervention among black men [27].…”
Section: Discussionmentioning
confidence: 84%
“…Another study conducted among Jamaican men found that there was an improvement in knowledge of PC risk factors and screening among men following an education intervention [ 24 ]. The effectiveness of community-based interventions on knowledge on PC has been reported across countries [ 17 , 25 , 26 ]. A similar study reported a significant increase in prostate cancer knowledge following a community health worker-led intervention among black men [ 27 ].…”
Section: Discussionmentioning
confidence: 99%